Analisis Kinerja Ruas Jalan dan Biaya Perjalanan akibat Tundaan pada Ruas Jalan (Studi Kasus Jl. Pangeran Antasari, Bandar Lampung) - Emmi Desniati; Rahayu Sulistyorini; Ika Kustiani (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
Pangeran Antasari Street plays an important role in serving and passing large number of traf - fics. The traffics, coupled with roadside barriers, cause delays in travel time. The purpose of this study is to analyze the performance of roads that is the level of service as well as the increase in travel costs due to delays. The assessment of the performance of the road section was carried out based on free flow traffics, which is the condition of the traffic flow without experi - encing delays and roadside obstacles. Performance values were obtained through a linear approach between the volume and speed of the vehicle using the Greenshield Model. Calculation of Vehicle Operating Costs (Biaya Operasional Kendaraan or BOK) of light vehicles and heavy vehicles were using a model developed by the Indonesian Research Affiliation Institute of the Bandung Institute of Technology (Lembaga Afiliasi Penelitian Indonesia Institut Teknologi Bandung or LAPI - ITB). Whereas the motorcycle BOK were useing the Road Traffic Services (Di - nas Lalu Lintas Angkutan Jalan or DLLAJ) method. The value of travel time was calculated based on the approach using the data of the City of Bandar Lampung's per capita income di - vided by the average number of working hours per year. The results showed that the service level of the Pangeran Antasari road segment was V / C > 0.8. This means that the road has a service level of D, which is near congested. The cost of congestion caused by traffic delays for the direction of Pangeran Antasari - Gajah Mada is Rp. 625.863.840/year, while for the direc - tion of Gajah Mada - Antasari is Rp. 845.009.609/year.